A common fixed point theorem for the $ψ$-contractive mapping - Chen, Chi-Ming; Chang, Tong-Huei (Tamkang Journal of Mathematics, 2010)
In this paper, we shall discuss the common fixed point theorems of four single-valued functions with $ψ$-contractive codition in cone metric spaces.